Development of thermostable microencapsulated lactobacillus targeted gut delivery / Muhamad Fareez Ismail - Ismail, Muhamad Fareez (Institute of Graduate Studies, UiTM, 2018)
Lactobacillus plantarum LAB 12, a lactic acid bacteria (LAB) strain isolated from local fermented food, possess probiotic characteristics. In spite of their chemopreventive properties, the vulnerability of LAB 12 during gastrointestinal transit (pH and enzymatic action) and industrial processing (heat and storage) remains a major concern. This study addressed these issues by immobilising LAB 12, by means of microencapsulation, within alginate (Alg)-based polymeric matrix, with incorporation of xanthan gum (XG) and coated with Ch (Alg-XG-Ch), or pea protein isolate (PPi; Alg-PPi). The physicochemical properties of Alg-based microcapsules were characterised by means of Fourier transform infrared (FTIR), X-ray diffraction (XRD) and differential scanning calorimetry (DSC) analysis. Survivability of microencapsulated LAB 12 exposed to simulated gastrointestinal fluids (pH 1.8 and pH 6.8), high temperatures and various storage conditions (4/8-week storage at 4 and 25 °C) were assessed. Pelletisation study was conducted to evaluate the survivability of microencapsulated LAB 12 subjected to actual heat challenge in industrial processing. The microencapsulated LAB 12 was further assessed for their safety through acute and subchronic toxicity studies in vivo. The fate and release of LAB 12 from Alg-based microcapsules in different rodent gut sections were examined by means of confocal microscopy and qPCR respectively. The chemopreventive properties of microencapsulated LAB 12 were validated using an orthotopic mouse model. The Alg-XG-Ch microcapsules diameter (1299-1343 Lim) were relatively outsized (> 350 \xm), a feature which could adversely affect sensory properties resulting in inappropriate mouth feel and flavour. Alg-PPi microcapsules, on the other hand were presented with a smaller diameter range (157.7-189.5 Lim) and could be an ideal microencapsulation system for LAB 12. This was based on their excellent tolerance against simulated gastric juice (96.4% survivability, intense heat (80.2% survivability at 100 °C for 30 minutes), storage (>7 log CFU g-1 after 8-week storage at 4 and 25 °C), pelletisation (89.4% survivability) and targeted release in simulated intestinal fluid (>9 log CFU g-1). The Alg-PPi LAB 12 microcapsules were used for all the susequent in vivo studies. For toxicity studies, no treatment (2.5 ><1010 CFU kg-1 BW) related adverse effects were observed in serum biochemistry and blood haematology. Histological sections of vital organs which included heart, kidney, lung, spleen, liver and gonads suggests that LAB 12 encapsulated in Alg-PPi were non-pathogenic and safe for consumption. As for the in vivo release study, the microcapsules were found intact in the stomach and LAB 12 were found to be present abundantly (>7 log CFU) only in the intestines. Also, orthotopic mouse model pre-fed with microencapsulated LAB 12 significantly (p < 0.05) reduced tumour volume (-98.87%) and weight (-89.27%) when compared to control. The chemopreventive effect could be possibly attributed to apoptosis and antiangiogenesis mediated. at least in part, through up-regulation of p53 (+32.50%) and caspase-3 (+92.61%), and down-regulation of COX-2 (-63.96%), VEGF (-65.93%) and PECAM-1 (-62.72%). Altogether, this study strongly implied the possibility of having the LAB12-loaded Alg-PPi microcapsules safely incorporated into various food types and nutraceutical products upon succesful completion of clinical trials.